A novel 3D porous modified material with cage-like structure: fabrication and its demulsification effect for efficient oil/water separation. Issue 12 (7th March 2017) - Wang, Zhongde; Xiao, Caiming; Wu, Zhijun; Wang, Yuting; Du, Xiao; Kong, Wei; Pan, Dahai; Guan, Guoqing; Hao, Xiaogang
Abstract : A modified 3D porous material with cage-like structure for efficient oil/water and emulsion separation. Abstract : A novel 3D porous copper foam (CF) with superhydrophobic or superhydrophilic properties is successfully fabricated and applied for oil/water and water-in-oil emulsion separations. The mechanical strength and pore size of the CF is easily tuned using an inexpensive and controllable electrodeposition method. A two-way channel separator is designed and made by the combination of two complementary modified CFs. It is found that such a system has a high separation efficiency and high-flux (about 186 800 L m −2 h −1 ) for continuous separation of oil/water with good reusability. Furthermore, due to the capillary tunnel effect in the material, the content of the oil in the purified water can be reduced to less than 20 ppm while the oil purity reaches higher than 99.99%. Surprisingly, the superhydrophobic CFs with a pore radius of less than 150 μm can completely separate the water-in-oil emulsion with high-flux (6560 L m −2 h −1 ) and high separation efficiency, and the oil purity reaches higher than 99.89%, even when the pore sizes are 7–30 times larger than those of droplet size in the water-in-oil emulsions. It is considered that the cage-like structure can promote demulsification and has a unique self-ascending effect, which can enhance demulsification by the micrometer-sized water droplet collision coalescence on gravity, and self-ascending coalescence. It is expected that such a technology can provide a new method for the separation of oil/water mixtures efficiently in a practical process.